Multicenter Analysis of Dosing Protocols for Sotalol Initiation. (May 2020) - Biswas, Minakshi; Levy, Andrew; Weber, Rachel; Tarakji, Khaldoun; Chung, Mina; Noseworthy, Peter A.; Newton-Cheh, Christopher; Rosenberg, Michael A.
Sotalol, a Vaughan-Williams Class III antiarrhythmic medication, is used to manage atrial arrhythmias. Due to its QT-prolonging effect and subsequent increased risk of torsade de pointes, many centers admit patients during the initial dosing period. Despite its widespread use, little information is available regarding dosing protocols during this period. In this multicenter investigation, dosing protocols in patients initiating sotalol therapy were examined to identify predictors of successful sotalol initiation. Over a 4-year period, patients admitted to 5 hospitals in the United States for inpatient telemetry monitoring during initiation for nonresearch purposes were enrolled. A 3-day course of 5 of 6 doses of sotalol was considered successful completion of the loading protocol. Of the 213 enrolled patients, over 90% were successfully discharged on sotalol. Significant bradycardia, ineffectiveness, and excessive QT prolongation were reasons for failed completion. Absence of a dose adjustment was a strong predictor of successful initiation (odds ratio: 6.6, 95% confidence interval: 1.3-32.7, P = .02). Hypertension, use of a calcium channel blocker, use of a separate β-blocker, and presence of a pacemaker were predictors of dose adjustments. Marginal structural models (ie, inverse probability weighting based on probability of a dose adjustment) verified that these factors also predicted successful initiation via preventing any dose adjustment and suggests that considering these factors may result in a higher likelihood of successful initiation in future investigations. In conclusion, we found that the majority of patients admitted for sotalol initiation are successfully discharged on the medication. The study findings suggest that factors predicting need for dose adjustment can be used to identify patients who could undergo outpatient initiation. Prospective studies are needed to verify this approach.